African American Living-Kidney Donors Should Be Screened for APOL1 Risk Alleles - Cohen, David M. (Transplantation, 2011)
The adjusted rate of end-stage kidney disease (ESKD) among African Americans is markedly increased relative to European Americans. African Americans are overrepresented on the kidney transplantation waiting list and experience longer wait times. In aggregate, these pressures drive recommendations for living donor transplantation. Genovese et al. recently implicated the APOL1 gene in ESKD risk among African Americans (Genovese et al. Science 2010; 329: 841). The presence of two APOL1 risk alleles doubles the relative risk for ESKD; moreover, the alleles are prevalent among African Americans. We propose a strategy for screening for the presence of APOL1 risk alleles among African American living kidney donors and for living-related donors for African American recipients.